O3 Large-scale helicobacter pylori (H. pylori) eradication aspirin trial (HEAT): results of a real-world outcomes study. (19th June 2022) - Hawkey, Chris; Avery, Tony; Coupland, Carol; Crooks, Colin; Dumbleton, Jennifer; Hobbs, Richard; Kendrick, Denise; Moore, Michael; Rubin, Greg; Smith, Murray
Abstract : Introduction: Helicobacter pylori (H. pylori) may be pivotal in the pathogenesis of upper gastrointestinal (UGI) ulcer bleeding from aspirin therapy. The Helicobacter Eradication Aspirin Trial (HEAT) investigated whether H. pylori eradication reduces the risk of UGI ulcer bleeding in aspirin users. Methods: HEAT was conducted using novel real-world methodology developed by the Simple Trials for Academic Research (STAR) group. Participants aged over 60 and taking aspirin ≤325mg daily for at least 4 months were recruited from primary care between 2012 and 2017. H. pylori positive participants were randomised to receive 7 days of eradication treatment (lansoprazole 30mg bd, clarithromycin 500mg bd and metronidazole 400mg bd) or matching placebos. Recruitment was managed using a bespoke web-based database that communicated directly with a programmed search tool downloaded at participating practices. It identified all suitable patients and automatically sent trial information and an invitation to participate. Effectiveness of H. pylori eradication was evaluated in a prospectively selected 10% sample by end of trial breath testing. Electronic follow up identified events in Hospital Episodes Statistics (HES), GP databases and patient reports. All episodes mentioning GI bleeding or peptic ulcer were evaluated by a blinded adjudication committee. The primary endpoint was a first hospitalisation due to definite or probable peptic ulcer bleeding, analysed using a Cox proportional hazards model. Data are still blinded and presented as Group A and B. Results: In total, 1, 208 GP practices across the UK sent 188, 875 invitation letters; 30, 166 patients were consented to the trial, of whom 5, 353 H . pylori positive participants (17.8%) were randomised. Mean age at consent was 73.6 ± 7.0 (SD) years and 72.1% of participants were male. In the 10% retest subjects 90.7% had become H. pylori negative in Group A vs 24.3% in Group B. The rate of presentation of UGI ulcer bleeding varied significantly by time. The rate of presentation varied significantly by time. Events occurred most frequently in the first 2–3 years of follow up in Group B when there appeared to be a significant difference between the groups. Fully analysed data will be available for presentation to the meeting Conclusions: Very large-scale real-world trials of clinical importance, such as H. pylori eradication in aspirin users can be successfully conducted in primary care using STAR methodology.